Social and educational movements and their impact on the school building programme in Budapest in around 1900 - Garai, Imre; Németh, András (Historia y Memoria de la Educación, 2020)
In our current study, we focus on school building program of Géza Bárczy who was the mayor of the Hungarian capital in the first two decades of the twentieth century. From the mid of the nineteenth century, Budapest had experienced a rapid development thanks to social and economic changes. The city council felt impelled to reflect on growing needs of the population of the city, therefore it launched a complex social program including renovating and building new school headquarters. Our main findings suggest that newly emerged school buildings stood in the frontier of different endeavours. Their structure and inner elements were influenced by pedagogues and intellectuals who were staunch supporters of reform pedagogy aiming at salvaging children from the harmful effects caused by traditional schooling. Furthermore, school buildings also represented the pride of the nation and the hope that talent members of future generations can preserve the fundamentals of the nation. It seems that the school building program of this area entailed these endeavours and even tried to reflect on them.